2011
DOI: 10.1158/1055-9965.epi-11-0363
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Levels in Nipple Aspirate Fluid and Serum during a Randomized Soy Trial

Abstract: Background Based on the hypothesized protective effect, we examined the effect of soy foods on estrogens in nipple aspirate fluid (NAF) and serum, possible indicators of breast cancer risk. Methods In a cross-over design, we randomized 96 women who produced ≥10 μL NAF to a high- or low-soy diet for 6-months. During the high-soy diet, participants consumed 2 soy servings of soy milk, tofu, or soy nuts (approximately 50 mg of isoflavones/day); during the low-soy diet, they maintained their usual diet. Six NAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 30 publications
(45 reference statements)
1
48
0
Order By: Relevance
“…Others who are willing to accept even smaller volumes have obtained sufficient NAF from 96% of subjects [14]. Maskarinec et al [8] considered 10 lL as the minimum for analysis and found that 36% of subjects met this criterion. Loud et al [15] considered 500 lL the minimum volume and found that 24% met this criterion in their population of BRCA1/2 carriers.…”
Section: Naf Yieldersmentioning
confidence: 99%
See 1 more Smart Citation
“…Others who are willing to accept even smaller volumes have obtained sufficient NAF from 96% of subjects [14]. Maskarinec et al [8] considered 10 lL as the minimum for analysis and found that 36% of subjects met this criterion. Loud et al [15] considered 500 lL the minimum volume and found that 24% met this criterion in their population of BRCA1/2 carriers.…”
Section: Naf Yieldersmentioning
confidence: 99%
“…Uptake of sulfated estrogens may also be affected [4,5]. Earlier studies of nipple aspirate fluid indicated that the concentration of estradiol is higher in the breast than in serum, and the coefficients of determination (the percent of the variance in breast fluid or tissue that can be accounted for by variation in serum) were generally less than 0.5 [6][7][8]. Nevertheless, the concentrations remain sufficiently constant over time within individuals to be useful as indicators of exposure of individuals [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association of serum estradiol with breast cancer risk [3] in postmenopausal women [46] and possibly in premenopausal women [7, 8], is relatively weak, perhaps because serum and tissue concentrations of estradiol are poorly correlated [9, 10]. For estradiol, several studies report correlations of 0.37 or less [1113], although a higher correlation has been reported recently in BRCA1/2 carriers [14]. Overall the results indicate that local formation of estradiol rather than simple diffusion from blood is the primary source of estradiol in the breasts of both pre- and postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…For each BEAN2 participant, four diluted NAF specimens equivalent to 4×10 μL NAF (baseline, month 3 or 6, month 7, and month 10 or 13) were sent to the Reproductive Endocrine Research Laboratory, at which E 2 and E 1 S were assessed using RIAs as described previously (13). …”
Section: Methodsmentioning
confidence: 99%